A Journey across the Nile - Nuayma, Mounir F.; Freidi Film Co.; Civilized Cultural Media ([Egypt] : Freidi Film Co.)
About civilization and antiquities of Egyption, includes the art of Egypt such as building of pyramid
Text, Dr. Mohamed Saleh ; cameraman, John Anderson
Keywords: Egypt -- Antiquities; Egypt -- Civilization; Archeology